2015
DOI: 10.1007/s00011-015-0899-5
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase negatively regulates the expression of proinflammatory cytokines and chemokines by zymosan-induced mouse neutrophils

Abstract: MPO deficiency upregulates the expression of several proinflammatory cytokines and chemokines in mouse neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Mpo − / − peritoneal cavity neutrophils stimulated in vitro with the toll-like receptor (TLR) 2 agonist zymosan, had increased production of proinflammatory MIP-1α, MIP-1β, IL-1α, IL-1β, and TNF-α as compared to WT [72]. This finding correlated to in vivo findings as indicated by a similar increase in the same cytokines in Mpo − / − mice following zymosan administration [72].…”
Section: Influence Of Mpo On Cytokine Production During Lung Inflamentioning
confidence: 75%
See 1 more Smart Citation
“…Mpo − / − peritoneal cavity neutrophils stimulated in vitro with the toll-like receptor (TLR) 2 agonist zymosan, had increased production of proinflammatory MIP-1α, MIP-1β, IL-1α, IL-1β, and TNF-α as compared to WT [72]. This finding correlated to in vivo findings as indicated by a similar increase in the same cytokines in Mpo − / − mice following zymosan administration [72].…”
Section: Influence Of Mpo On Cytokine Production During Lung Inflamentioning
confidence: 75%
“…Mpo − / − peritoneal cavity neutrophils stimulated in vitro with the toll-like receptor (TLR) 2 agonist zymosan, had increased production of proinflammatory MIP-1α, MIP-1β, IL-1α, IL-1β, and TNF-α as compared to WT [72]. This finding correlated to in vivo findings as indicated by a similar increase in the same cytokines in Mpo − / − mice following zymosan administration [72]. Similarly, it was found that Mpo − / − mice with zymosan-induced lung inflammation exhibited elevated levels of MIP-2, which correlated with increased number of neutrophils in the lung [73].…”
Section: Influence Of Mpo On Cytokine Production During Lung Inflamentioning
confidence: 99%
“…Previous studies have reported similar or altered neutrophil tissue infiltration for MPOdeficient mice in various disease models[38][39][40][41][42][43][44][45] which could affect oxidative stress levels. However, in the typhoid fever model neutrophil recruitment as detected by an antibody to Ly-6G was similar in infected wild-type and MPO-deficient mice(Fig.…”
mentioning
confidence: 99%
“…Upon encountering the host immune cells, Aspergillus induced neutrophil degranulation, from which MPO had the capacity to attenuate TNF‐α. Indeed, MPO deficiency in mice had been reported to exacerbate inflammation and pneumonia with concurrent increased pro‐inflammatory cytokine levels (Endo, Saito, Umeki, Suzuki, & Aratani, ; Homme, Tateno, Miura, Ohno, & Aratani, ). On the other hand, the modulation of IL‐1β was dependent on cellular contact through the involvement of CR3.…”
Section: Discussionmentioning
confidence: 87%